2018
DOI: 10.1093/icvts/ivy049
|View full text |Cite
|
Sign up to set email alerts
|

Carotid stenosis with impaired brain flow reserve is associated with an increased risk of stroke in on-pump cardiovascular surgery†

Abstract: Carotid stenosis is a risk factor for perioperative stroke in on-pump surgery. Patients with large Stage 2 area (>10%) are at increased risk of perioperative stroke when on-pump surgery is performed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 17 publications
0
6
0
1
Order By: Relevance
“…International guidelines recommend carotid duplex ultrasound in patients with previous stroke who have had an event within 6 months or have significant risk factors 21 . In select patients with severe cerebrovascular atherosclerosis, off‐pump CABG should be considered as the preferred approach to reduce risk of perioperative stroke 22,23 . By avoiding the risks associated with aortic cannulation and cross‐clamping, off‐pump CABG has been demonstrated to improve neurological outcomes in patients with a history of previous cerebrovascular events 24 .…”
Section: Discussionmentioning
confidence: 99%
“…International guidelines recommend carotid duplex ultrasound in patients with previous stroke who have had an event within 6 months or have significant risk factors 21 . In select patients with severe cerebrovascular atherosclerosis, off‐pump CABG should be considered as the preferred approach to reduce risk of perioperative stroke 22,23 . By avoiding the risks associated with aortic cannulation and cross‐clamping, off‐pump CABG has been demonstrated to improve neurological outcomes in patients with a history of previous cerebrovascular events 24 .…”
Section: Discussionmentioning
confidence: 99%
“…While CABG has played a significant role in revascularization for ischemic heart disease, neurological complications have been a primary concern. In particular, CIAD increases perioperative stroke and mortality risk [1, 2].…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, large retrospective studies have shown OPCAB to be associated with a lower incidence of stroke compared with that using conventional on-pump CABG [13, 14]. Particularly in high risk patients, such as those with cerebrovascular atherosclerosis, severe aortic atherosclerotic, or peripheral artery disease, OPCAB reduced stroke incidence [2, 15]. Therefore, we selected OPCAB for this patient.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Besonders Patienten mit vorbestehender Vasosklerose und Stenosen der hirnversorgenden Gefäße sind gefährdet, in der perioperativen Phase einen thrombotischen Gefäßverschluss zu erleiden [14,15,31] onshemmern (PAH) oder Antikoagulanzien verstärkt wird [11,27]. Hämodynamische Infarkte, die durch zerebrale Hypoperfusion im Rahmen von hypotonen Episoden auftreten können und Grenzzonengebiete betreffen, machen einen geringen Anteil aller perioperativen Schlaganfälle aus [27].…”
Section: äTiologie Und Risikofaktorenunclassified